BRAND IMAGE, SOCIAL DIGITAL MARKETING, AND PRODUCT INNOVATION ON CONSUMER SATISFACTION OF CHATIME DRINKS IN PEKANBARU - Achmad Tavip Junaedi; Dhea Anggelina; Nicholas Renaldo; Suhardjo Suhardjo; Jahrizal Jahrizal; Emiliana Shania Meta Nahak (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The purpose of this study was to determine and analyze the effect of brand image, social digital marketing, and product innovation on consumer satisfaction of Chatime drinks in Pekanbaru. This research was conducted in Pekanbaru City. The time of this research started from September 2023 and ended in December 2023. This research was conducted in Pekanbaru City on people who had bought Chatime drinks. Because the population is not known for certain, using the Roscoe approach, the number of samples was determined as 120 people using the purposive sampling technique. Data analysis used multiple linear regression. The results of the study explain that brand image has a positive and significant influence, then social digital marketing also has a positive and significant influence, and product innovation also has a positive and significant influence on consumer satisfaction with Chatime drinks in Pekanbaru. Tujuan dalam penelitian ini adalah untuk mengetahui dan menganalisis pengaruh brand image, sosial digital marketing dan inovasi produk terhadap kepuasan kinsmen minuman Chatime di Pekanbaru. Penelitian ini dilakukan di kota Pekanbaru. Waktu penelitian ini dimulai dari bulan September 2023 dan berakhir pada bulan Desember 2023. Penelitian ini dilaksanakan di kota Pekanbaru pada masyarakat yang pernah melakukan pembelian minuman Chatime. Karena populasi dalam tidak diketahui jumlahnya dengan pasti, maka dengan pendekatan roscoe ditetapkan jumlah sampel sebanyak 120 orang menggunakan teknik purposive sampling. Analisis data yang digunakan regresi linier berganda. Hasil penelitian menjelaskan bahwa brand image memiliki pengaruh positif dan signifikan, selanjutnya sosial digital marketing juga berpengaruh positif dan signifikan dan inovasi produk juga memiliki pengaruh positif dan signifikan terhadap kepuasan konsumen minuman Chatime di Pekanbaru.